Essential practical NMR for organic chemistry / S.A. Richards, J.C. Hollerton. - Richards, S. A.; Hollerton, J. C. (John C.), 1959- (Wiley, 2023)
A hands-on resource advocating an ordered approach to gathering and interpreting NMR data. The second edition delivers a pragmatic and accessible text demonstrating an ordered approach to gathering and interpreting NMR data. In this informal guide, you'll learn to make sense of the high density of NMR information through the authors' problem-solving strategies and interpretations. The book also discusses critical aspects of NMR theory, as well as data acquisition and processing strategy. It explains the use of NMR spectroscopy for dealing with problems of small organic molecule structural elucidation and includes a new chapter on Nitrogen-15 NMR.